STRATEGI GURU SD MELAKSANAKAN PEMBELAJARAN MATEMATIKA SELAMA PANDEMI COVID-19 - Aprisal Aprisal; Sartika Arifin; Yunda Victorina Tobondo (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Through mathematics students can develop various abilities such as: reasoning ability, analytical thinking ability, critical thinking ability and problem solving ability. During the COVID-19 pandemic, teachers are required to maintain the substance of the mathematics material taught to students. This study aims to describe and analyze the teacher's strategy in implementing online mathematics learning at the elementary school level. The sample of this study was elementary school teachers totaling 129 people spread over 33 elementary schools in the South Sulawesi region. The instrument used in the study to collect data was in the form of a strategy questionnaire for elementary school teachers to carry out mathematics learning and interview guidelines. Data analysis techniques in this study consist of data reduction, presenting data, and drawing conclusions. Based on the results of the study, it was concluded that online learning was not more effective than face-to-face learning in class. However, various strategies are carried out by teachers to overcome these problems so that online mathematics learning can be carried out in accordance with the needs of students. These strategies include: making learning videos, building good communication with parents, providing additional lesson hours, forming small study groups for students, encouraging parents to participate in learning so that they can assist teachers in guiding children to study at home.